MECHANICAL DESIGN AND OPTIMISATION OF LUMBAR DISC PROSTHESIS MODEL - Lee K.Y.S.; Tan W.J.; Ramesh S.; Mahdi Al-Obaidi A.S.H. (Taylor's University, 2024)
The effect of dimensions on the safety factor, allowable stress, and deformation of the lumbar disc prosthesis model at L4-L5 was investigated. The process involved geometry design, meshing, enhancement in element quality, and setting of boundary conditions using SolidWorks and ANSYS software. The range of motion (ROM) of flexion and extension were measured using SolidWorks Limit Angle. Additionally, the direct optimisation method was utilised to determine the optimal input parameters and dimensions for the lumbar disc prosthesis model. The results showed a wide ROM for flexion and extension of the model, which ranged from 20 to -11 when Polyetheretherketone (PEEK) was selected as the biomaterial. The distribution of stress and deformation of the model during neutral, flexion and extension are presented. An overview of the optimised dimensions that satisfied the requirements for safety factor (more than 2), allowable stress (70.2 MPa) and deformation (62.11 ?m) for the model are deliberated. Three optimised input diameters and heights of 10.2 mm x 0.279 mm, 11.4 mm 1.591 mm and 13 mm x 1.810 mm were proposed for the lumbar disc prosthesis model. The safety factor, maximum stress and deformation of the proposed dimensions ranged from 2 to 2.11, 52.32 to 55.12 MPa and 30.14 to 37.98 ?m, respectively. School of Engineering, Taylors University.